The Influence of Rib Configuration on Bond Strength Development between Steel and Concrete - Shoib Bashir Wani; Dar Sarvat Gull; Ishfaq Amin (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2020)
The bond strength between rebar and concrete is important for the quality performance of reinforced concrete structures. At the interface, bond strength development mainly depends on surface configuration. Different rib configuration improves the strength significantly in high yield rebars as compared to mild steel. This study examines the bond strength behavior of ordinary MS (Mild Steel) rebars, HYSD (High Yield Strength Deformed) parallel rib, and HYSD diamond rib rebars. Experimental analysis to obtain pull-out behavior of rebar in concrete was based on IS 2770 Part I – 1967: Reaffirmed 2007; Indian Standard Methods of Testing Bond in Reinforced Concrete. Importantly, the concrete of M30 grade was used and a total of nine specimens were tested. The cubes of size 150mm x 150mm x 150mm were cast with centrally embedded rebar provided up to 20 mm from their bottom faces. Additionally, the pull-out test was conducted in 1000 kN capacity Universal Testing Machine. The usable bond strength values were calculated from the load at 0.025 mm free and 0.25 mm loaded end slips. The results showed that the usable bond strength value of HYSD diamond rib rebars is very large compared to MS and appreciably greater than HYSD parallel rib. Moreover, the usable bond strength of HYSD diamond rib rebars is 60.06% and 35.60 % greater than that of the MS rebars and HYSD parallel rib pattern rebars, respectively. The high frictional resistance developed in the bond strength test of HYSD diamond rib rebars because of the better mechanical interlocking. This was primarily due to the presence of a more frictional surface area of lugs.